Foreword (Acta Linguistica Asiatica)
Studying the Korean language serves as a vital key to understanding the interconnected realms of linguistics, history, culture, literature, and education. This issue seeks to highlight the richness of contemporary Korean Studies through a diverse collection of articles spanning these various fields. Notably, this edition showcases the passion and interest in Korean linguistics from scholars across Europe, Asia, and the United States. Through the global engagement, we envision the potential for building a new Korean Studies network and, ultimately, fostering an expanded network for Asian Studies.